Market analysis of photovoltaic solar energy systems with emphasis on brazilian rural area (Research, Society and Development, 2023)
Solar energy is a renewable electricity source that can be captured and converted by solar panels, making it an interesting option to supply geographically isolated areas. The aim of this study is to carry out a market analysis of photovoltaic solar systems for residential and commercial use, as well as to gather information about the traditional (fixed) and mobile (solar tracking) structure, with an emphasis on better energy efficiency for use in remote rural areas in Brazil. In this sense, the estimated and real cost for the traditional assembly of photovoltaic solar systems in the last 10 years was analyzed, as well as an analysis of the implementation of mobile assembly in relation to the current market through the PEST and SWOT methodologies. It was pointed out that a mobile solar photovoltaic system with solar tracking tends to generate more electricity than a fixed-mount one, however, its cost is higher due to the electrical devices needed to carry out the movement. In this case, more detailed information on costs was not found in the literature. It was also pointed out that currently the implementation of a photovoltaic solar system (fixed assembly) is around R$ 4.88/Wp for residential use and R$ 3.88/Wp for commercial use, with a tendency to decrease over the years. For future studies, it is proposed to survey costs for the implementation of solar photovoltaic systems with single-axis and dual-axis solar trackers, to understand whether the better energy efficiency generated is an advantage in relation to its assembly cost.